TINJAUAN VIKTIMOLOGI TERHADAP ANAK KORBAN KEKERASAN SEKSUAL SESAMA JENIS BERDASARKAN PUTUSAN NOMOR : 119/PID.SUS/2023/PN. Tjk. - Rafiqo Mauli Novita; I Ketut Seregig, Yulia Hesti (JOURNAL OF LAW AND NATION, 2024)
Referring to national data in the Online Information System (SIMFONI PPA), cases of sexual violence against children have increased over the past few years, namely in 2019 the number of cases of violence against children was recorded at 11,057 cases and increased by 11,278 in 2020. Then, a significant increase occurred in 2021, which reached 14,517 cases, until 2022 the number of sexual violence reached 16,106 cases. In Lampung Province, data on sexual violence against children in 2021 reached 681 cases, in 2022 it decreased to 600 cases, but in 2023 it again increased, reaching 696 cases. This series of data suggests that Indonesia is known as a polite nation, but the rate of sexual violence in this country is quite high. This situation further strengthens the assumption that Indonesia, especially Lampung Province, is in a state of sexual violence emergency. Currently, cases of sexual violence against children are not only focused on girls, boys are often victims of sexual crimes by perpetrators who have disorders or deviations. sexual. Sexual violence committed against children can be seen from a victimology perspective. Victimology is a complement or refinement of existing theories of criminal etymology according to the actual proportions dimensionally. The aim of this research is to discuss how victimization results in children becoming victims of same-sex sexual violence. This research uses qualitative methods and case study research type, using the theory put forward by Stephen Schafer,  a  criminologist  and  sociologist,  where  the  focus  of  the theory that the author uses in this research is victim typology theory, this theory explains  how victims  are  consciously or unconsciously contributed to the victimization he suffered. From this problem, researchers see several aspects that can trigger victims. Apart from that, the role of the government, community institutions and parents is needed to combat child predators and provide countermeasures for child victims of sexual violence.